Determination of Fluid Viscosity Coefficient Using jetAudio and Subtitle Edit - Haris Rosdianto; Emi Sulistri; Anis Nazihah Mat Daud (STKIP Singkawang, 2019)
The purpose of this study is to produce an experimental design for determining the viscosity coefficient using jetAudio and Subtitle Edit software, and determining the value of the fluid viscosity coefficient by using this experimental design. In this study, the type of fluid used is packaged cooking oil, and the object used is a magnetic ball. The method proposed by the author to measure the travel time of the magnetic ball in cooking oil is by using the combination of coil sensors, jetAudio, and Subtitle Edit. JetAudio software will record magnetic induction traces as the magnetic ball passes the coils into audio format, Subtitle Edit software is used to determine travel time of the magnetic ball based on jetAudio recording data. The results of this study are jetAudio and Subtitle Edit can be used in fluid viscosity coefficient experiments. The value of the cooking oil viscosity coefficient obtained from this study is 0,561431096 Pa.s.